Cationic surfactants: a review - Gonçalves, Rui A. (2023)
Cationic surfactants have gained significant interest since their introduction. Their properties and adsorption behavior onto different surfaces have driven the development of a plethora of surfactants with distinctive functionalities. This paper reviews self-assembly, intermolecular interactions, and the properties of cationic surfactants also when interacting with co-solutes, which may be small molecules or macromolecules, and surfaces. The versatile properties of single- and double-chain cationic surfactants and other special cationics such as gemini, catanionic, bolaform, amino acid- and sugar-based surfactants, are presented and discussed together with skin toxicity and environmental considerations. The effects of cationic surfactant mixing with other surfactants, polymers, proteins, and DNA are also shown and examined. We also outline established applications of cationic surfactants as disinfectants, in fabric softening, hard surface cleaning, personal care applications, road surfacing, and oil field applications, as well as emerging applications such as soft antimicrobial agents and nucleic acid delivery, which has contributed, for instance, to the enormously successful surfactant-based mRNA COVID-19 vaccines.